2006
DOI: 10.1212/01.wnl.0000247107.54562.0e
|View full text |Cite
|
Sign up to set email alerts
|

Two randomized vitamin D trials in ambulatory patients on anticonvulsants

Abstract: In ambulatory adults on antiepileptic drugs, high-dose vitamin D therapy substantially increased bone mineral density at several skeletal sites. In children, both doses resulted in comparable increases in bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 25 publications
2
73
1
6
Order By: Relevance
“…However, in this study osteocalcin levels were not significantly affected in the phenytoin group, but they were increased in rats treated with valproic acid and increased with low-dose levetiracetam [305]. Although clinical studies have shown that these effects on bone density may be attenuated by vitamin D 3 treatment [306], more studies are needed to assess the effects of anticonvulsants on bone strength [307].…”
Section: Anticonvulsantscontrasting
confidence: 54%
See 1 more Smart Citation
“…However, in this study osteocalcin levels were not significantly affected in the phenytoin group, but they were increased in rats treated with valproic acid and increased with low-dose levetiracetam [305]. Although clinical studies have shown that these effects on bone density may be attenuated by vitamin D 3 treatment [306], more studies are needed to assess the effects of anticonvulsants on bone strength [307].…”
Section: Anticonvulsantscontrasting
confidence: 54%
“…Treatment of anticonvulsantinduced alterations of vitamin D with replacement therapy of 400e4000 IU/day of vitamin D 3 has been shown to be effective in normalizing parameters of mineral metabolism and improving bone mass [306,357,358]. In addition, treatment of anticonvulsant osteomalacia with small doses of oral 25(OH)D has also proved effective [315].…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…Hannan et al (2008) showed that serum 25-hydroxyvitamin D and BMD were significantly related to one another in white men only. Mikati et al (2006) conducted the only randomized, controlled trial that demonstrated no significant difference between high-and low-dose vitamin D treatments, and no change in BMD compared with healthy controls after one year of treatment. Although there is no consensus on optimal vitamin D levels, many physicians often rely on 25-hydroxyvitamin D levels to evaluate bone health.…”
Section: Discussionmentioning
confidence: 99%
“…IU per day for adults and 2000 IU per day for children)[46, Class II]. In the adults, the baseline BMD was reduced at all sites when compared with controls matched for age and gender.…”
mentioning
confidence: 99%